Preexposure Prophylaxis Outcomes in an Urban Community in North Carolina: Discontinuation of Care and Sexually Transmitted Infections. Issue 3 (30th March 2021) - Clement, Meredith Edwards; Nicchitta, Mira; Sun, Ying; Ellis, Alicia; Chakraborty, Hrishikesh; McGee, Kara; Eagle, Cedar; Frye, Justin; Taylor, Destry; Okeke, Nwora Lance; Johnston, Barbara; Seña, Arlene C.; et al.
Abstract : A study of preexposure prophylaxis users in North Carolina found that programs were reaching high rates of racial/ethnic minority patients. However, rates of discontinuation were high and rates of sexually transmitted infections were moderate. Abstract : Background: Few studies have examined long-term outcomes among persons who initiate preexposure prophylaxis (PrEP) in the South, including PrEP discontinuation and sexually transmitted infection (STI) rates. Methods: Care discontinuation (>6 months without a PrEP appointment) and incident STIs were evaluated for patients at 2 PrEP clinics in Durham, NC. We tested for predictors of discontinuation as a binary variable using logistic regression. Model covariates included age, race/ethnicity, sex, known HIV-positive partner, commercial sex work, men who have sex with men (MSM) versus not MSM, type of insurance, and clinic site. A similar analysis was completed for STI incidence, controlling for days in the study. Results: Among 271 patients, mean age was 33.2 years, 46.9% were Black and 11.1% were Latino, 81.2% were MSM, and 32% were uninsured. Preexposure prophylaxis was discontinued in 47%, and another 11% had intermittent care. Sexually transmitted infection incidence was 45.4/100 person-years, and 5 patients were diagnosed with HIV at baseline or in follow-up. Men who have sex with men were less likely to discontinue PrEP relative to non-MSM (odds ratio [OR], 0.26; 95% confidence interval [CI], 0.10–0.64). Baseline STI was associated with a higher likelihood of incident STI (OR, 8.19; 95% CI, 3.69–19.21), whereas care discontinuation was associated with a lower likelihood of STI (OR, 0.28; 95% CI, 0.11–0.65). Conclusions: Preexposure prophylaxis programs in the Southern United States are reaching uninsured and predominantly Black and Latino MSM, but discontinuation rates are high despite elevated rates of incident STI and HIV. Further work is required to elucidate causes of PrEP discontinuation and encourage persistence in care.